The concept of childhood analyzes the basic education - doi: 10.4025/actascieduc.v35i2.20639 - Anete Abramowicz; Fabiana de Oliveira (Universidade Estadual de Maringá, 2013)
Current discussion deals with an understanding of childhood asan analytical category that visualizes the child within early childhood education and elementary education to provide reflections and challenges for the school in its endeavor to organize time and space as from the concept of childhood. The understanding of childhood will be undertaken from the three-fold axis of time, experience and invention. The essay will show how the concept of childhood should address early childhood education to primary education and investigate a type of early childhood education that would implement and not prevent the exercise of childhood.